Tawhid Paradigm as Foundation in Islamic Education Philosophy: Theological-Normative Review Analysis - Muhammad Rafliyanto (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This article aims to describe the concept of tawhid paradigm as a philosophical foundation in the study of Islamic education philosophy through theological-normative review. In its implementation, often the concepts and goals of Islamic education encounter problems that are not coherent with the dogmatic teachings of Islamic theology, where there are still many educational institutions that lead to western education. The purpose of this research is to describe the concept of tawhid which is used as a foundation of Islamic theology in the study of the philosophy of Islamic education. This research uses a qualitative method through a library research approach. The data collection technique used by researchers uses a type of content analysis technique. The results of this study explain that tawhid as the basis of theological studies in the philosophy of Islamic education provides a concept and idea not only in the field of education, in its implementation the essence of tawhid also aims to shape the morality of society, especially in Muslims. Then, the aspects of tawhid and education have a mutually bound relationship to provide aworldview that is oriented not only to worldly needs, but also ukhrawi. In epistemology, monotheism as the basis of theological studies is also the basis of activity for every Muslim and systemically will be built into a concept of manifesting Islam.